2019
DOI: 10.1038/s41598-018-36685-6
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Oxidation of the Hole Transport Layer in Perovskite Solar Cells by A Low-Temperature Plasma

Abstract: Herein we report a strategy of rapid oxidation of the hole transport layer (HTL) in perovskite solar cells by using oxygen/argon mixture plasma. This strategy offers a promising approach for simple manufacturing, mass production, and industrial applications. Compared to the conventional process of overnight oxidation, only ~10 s of oxygen/argon mixture plasma treatment is enough for the solar cell devices with FTO/ETL/perovskite/HTL/Au structure demonstrating a high power conversion efficiency. It is found tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 34 publications
2
17
0
Order By: Relevance
“…On the other hand, Ar was chemically inert. No noticeable oxidation and mobility enhancement were observed for the LiTFSI-doped spiro-OMeTAD HTL exposed to Ar plasma [20]. In addition, noticeable surface/structure modification, such as sputter etching was hardly observed under our low-energy plasma process within several seconds either (Figure 5), which was also demonstrated in another very recent work [29].…”
Section: Resultssupporting
confidence: 80%
See 2 more Smart Citations
“…On the other hand, Ar was chemically inert. No noticeable oxidation and mobility enhancement were observed for the LiTFSI-doped spiro-OMeTAD HTL exposed to Ar plasma [20]. In addition, noticeable surface/structure modification, such as sputter etching was hardly observed under our low-energy plasma process within several seconds either (Figure 5), which was also demonstrated in another very recent work [29].…”
Section: Resultssupporting
confidence: 80%
“…Mobility of LiTFSI-doped spiro-OMeTAD was increased by more than one order of magnitude within less than 10 s plasma exposure. The results of mobility enhancement explained our previous work which demonstrated that ~10 s plasma exposure can result in the appreciable operation of PSC devices employing LiTFSI-doped spiro-OMeTAD HTL [20]. Typically, more than several hours of exposure to H 2 O, O 2 or dry air were necessary to functionalize LiTFSI-doped spiro-OMeTAD HTL and obtain desirable PSC device performance [10,12,14,15].…”
Section: Resultssupporting
confidence: 73%
See 1 more Smart Citation
“…The synthesis and study of the properties of new spiro‐fused carbo and heterocyclic compounds are one of the priority areas of investigations in organic chemistry, the results of which are of both theoretical interest and practical importance for a large number of researchers. These studies have been presented to the chemical community in original articles, [1–26] in thematic reviews, [27–35] as well as in review articles on the synthesis of some other heterocycles where spiro analogs are mentioned in one way or another [36,37] . The topic of spiro‐fused heterocycles is quite wide and therefore often touched upon when studying the chemistry of natural compounds, [38,39] in review articles [40] on the use of individual organic compounds in the synthesis of alkaloids, [41] in the enantioselective synthesis of hetero and carbocycles [42] or their macrocyclic analogs [43,44] …”
Section: Introductionmentioning
confidence: 99%
“…61 However, the presence of lithium cation was demonstrated to accelerate the oxidation process as well as the degradation of iodidebased solar cells, attributing the photovoltage losses to the presence of this ion. 62,63,64 In the same way, this result came into a controversy situation due to the recent study in 28 Chapter 1 bromide-based materials, suggesting different consequences in the performance of the PSCs depending on the halide compound employed. 58…”
Section: Spiro-ometadmentioning
confidence: 99%